2012
DOI: 10.11144/javeriana.sc17-3.eodp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of donor plant age and explants on in vitro culture of Cedrela montana Moritz ex Turcz

Abstract: Abstract. To evaluate the organogenic potential of Cedrela montana Moritz ex Turcz, explants from mature (10-20 year-old) and juvenile (7-18 month-old) trees were collected. The first grouping included buds, leaves, and nodes derived from juvenile basal offshoots and rejuvenated shoots from cuttings. The second, included leaves, petioles, nodes, internodes and nodes of in vitro elongated shoots. The highest organogenic potential was observed in nodes from juvenile trees: 45.8% of explants presented axillary bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
3
5
0
6
Order By: Relevance
“…Los resultados del estudio coinciden con los obtenidos por Basto et al (2012) en donde segmentos nodales de Cedrela montana Moritz ex Turcz, provenientes de individuos adultos e introducidos en cultivo in vitro, tuvieron una baja respuesta organogénica, observándose sólo un 6,7% de los segmentos nodales cuya yema axilar presentó elongación.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Los resultados del estudio coinciden con los obtenidos por Basto et al (2012) en donde segmentos nodales de Cedrela montana Moritz ex Turcz, provenientes de individuos adultos e introducidos en cultivo in vitro, tuvieron una baja respuesta organogénica, observándose sólo un 6,7% de los segmentos nodales cuya yema axilar presentó elongación.…”
Section: Resultados Y Discusiónunclassified
“…Todo tejido maduro pierde potencial morfogénico debido a la determinación celular que lleva a una especialización de tejido, lo que reduce la plasticidad y la capacidad de diferenciación de las células (Basto et al 2012). Esto puede explicarse por el hecho de que en etapa de madurez, los genes se expresan en forma diferencial con respecto a los tejidos juveniles (García et al 2000).…”
Section: Resultados Y Discusiónunclassified
“…Srinidhi et al (2008) reported that nodal explants excised from the juvenile seedlings (1.5-year-old) of Azadirachta indica were more effective for shoot induction and rooting than the explants excised from the mature trees (15-year-old). Further, Basto et al (2012) observed the highest organogenic potential in nodes from juvenile (7-18 month-old) trees and found that material from mature trees (10~20 year-old) had limited organogenesis. Similarly, Tawfik et al (2020) reported axillary shoot induction from nodal explants excised from in vitro-grown juvenile seedlings (5-week-old) of Koelreuteria bipinnata, however the nodal explants from mature trees (20-year-old) did not develop any axillary shoots.…”
Section: Shoot Induction From Juvenile and Mature Sourcesmentioning
confidence: 97%
“…Malgré ce fait, peu de travaux se sont penchés sur l'introduction d'agents antimicrobiens dans les milieux de culture chez l'ananas. Outre les facteurs exogènes tels que les facteurs environnementaux (température, lumière, luminosité, hygrométrie, photopériode) et ceux du milieu de culture tels que la composition saline et les régulateurs de croissance, des facteurs intrinsèques à l'explant comme la position (Houédjissin et al, 2015 ;Acheampong et al, 2015) et l'âge (Basto et al, 2012) déterminent l'orientation de la culture. L'influence de la position de l'explant chez Ananas comosus var.…”
Section: Introductionunclassified
“…La position et l'âge déterminent donc significativement chez tous les cultivars le comportement des bourgeons. De pareilles observations ont été faites par Basto et al (2012) sur Cedrela montana où les explants (bourgeons, noeuds, feuilles, pétiole et entre-noeuds) provenant de plants âgés avaient plus de mal à régénérer in vitro par rapport aux explants provenant de plants jeunes. Concernant l'effet de la position, Acheampong et al (2015) ont fait de similaires observations sur les bourgeons de cayeux de tige d'ananas, où les bourgeons apicaux et médians ont respectivement présenté des taux de régénération de 95% et 90% par rapport aux bourgeons basaux qui ont eu un taux de régénération de 65%.…”
Section: Introductionunclassified